PENGARUH KEPERCAYAAN MEREK, DESAIN PRODUK DAN FANATISME TERHADAP LOYALITAS PELANGGAN SEPATU CASUAL ADIDAS PADA GEN-Z DI SOLO RAYA - Dila tri yuliana; Budi istiyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research was conducted with the aim of finding out whether there is an influence of brand trust, product design and fanaticism on customer loyalty for Adidas casual shoes among Gen-Z in Solo Raya. The population in this study is not limited to gen-z in Solo Raya. The sampling method uses non-probability sampling with purposive sampling technique. The total sample was 80 respondents. This research uses quantitative methods and collects data using a questionnaire in the form of a Google form. The data analysis methods used in this research are instrument testing, classical assumption testing, and multiple linear regression analysis with the SPSS application program. The results of this research show that the Brand Trust and Product Design variables do not have a significant effect on Customer Loyalty, while the Fanaticism variable has a significant positive effect on Customer Loyalty.